Foundations of Multi-Factor Parametric Modeling for the Occupational Safety Management System in Industrial Enterprises - Dostkabilovich, Rahimov Oktyabr; Yakhshiboy Kizi, Yarasheva Manzura (EDUMALSYS Journal of Research in Education Management, 2026)
This article examines the significance of hazard identification and risk assessment in ensuring effective labor protection in industrial enterprises, emphasizing their central role in preventing occupational incidents and improving safety management. It aims to clarify the content and essence of hazard identification, explain how systematic identification underpins robust risk assessment, and outline methodological approaches for determining the full set of hazards and their parameters. Adopting a systems-analysis perspective, the article describes how multi-factor experimental design and systematization methods can be applied to capture the interaction of multiple variables and to structure complex hazard information in industrial settings. The discussion highlights that the combined use of these methods enables a more comprehensive and precise mapping of hazards and their characteristics, thereby strengthening the reliability of risk assessments and supporting evidence-based decisions in labor protection. The article concludes that integrating hazard identification with multi-factor and systemic analytical approaches offers a methodological foundation for enhancing occupational risk management and refining safety strategies in industrial enterprises.